2012
DOI: 10.1097/aln.0b013e318242a48c
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Neurotoxicity Is Mediated by p75 Neurotrophin Receptor Activation

Abstract: Background Propofol exposure to neurons during synaptogenesis results in apoptosis leading to cognitive dysfunction in adulthood. Previous work from our laboratory showed that isoflurane neurotoxicity occurs through p75 neurotrophin receptor (p75NTR) and subsequent cytoskeleton depolymerization. Given that isoflurane and propofol both suppress neuronal activity, we hypothesized that propofol also induces apoptosis in developing neurons through p75NTR. Methods DIV5-7 neurons were exposed to propofol (3 µM) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 52 publications
6
101
2
2
Order By: Relevance
“…According to the study by Lemkuil et al (30), isoflurane induced neurotoxicity in rats by activating p75 NTR -RhoA, while inhibition of the activity of RhoA reversed the neurotoxicity of isoflurane. In addition, Pearn et al (31) reported that p75 NTR and RhoA kinase activation were involved in propofol-induced apoptosis in developing neurons in vitro and in vivo. The present study added novel results regarding the roles of caspase-3 and cleaved-PARP in sevoflurane exposure-induced cognitive impairment, and highlighted the importance of caspase-3 and cleaved PARP in the pathogenesis of nervous system dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Lemkuil et al (30), isoflurane induced neurotoxicity in rats by activating p75 NTR -RhoA, while inhibition of the activity of RhoA reversed the neurotoxicity of isoflurane. In addition, Pearn et al (31) reported that p75 NTR and RhoA kinase activation were involved in propofol-induced apoptosis in developing neurons in vitro and in vivo. The present study added novel results regarding the roles of caspase-3 and cleaved-PARP in sevoflurane exposure-induced cognitive impairment, and highlighted the importance of caspase-3 and cleaved PARP in the pathogenesis of nervous system dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Lemkuil et al (11) demonstrated that isoflurane induced neurotoxicity of mouse neurons by activating p75 NTR -RhoA, and inhibiting activation of RhoA attenuated isoflurane-induced impairment. Pearn et al (12) also reported that propofol-induced apoptosis is involved in p75 NTR and RhoA kinase activation in developing neurons in vivo and in vitro. These suggested that RhoA played important roles in the neurotoxicity of anesthetics.…”
Section: Introductionmentioning
confidence: 97%
“…[12,21,22] Almost all anesthetics were involved when administered to individuals in phases where there is neural development and synaptogenesis, except for some adjuvants such as α2-agonists. [13][14][15]21] Some studies suggest that dexmedetomidine administered as a preanesthetic medication possesses a neuroprotective effect, reducing the neurotoxicity induced by propofol and isoflurane. [16,21,25] The mechanism by which local anesthetics trigger its neurotoxic effects involves induction of apoptosis, which starts with the increased conductance of the calcium channels, with an increase of the intracellular concentration of this, production of reactive oxygen species and release of cytochrome c into the cytosol, culminating with the induction of caspases formation, decrease of the expression of anti-apoptotic proteins (Bcl-2) and increased expression of pro-apoptotic proteins (BAX), inducing acceleration of programmed cell death.…”
Section: Discussionmentioning
confidence: 99%